Children’s Mental Health in Southwestern Ontario during Summer 2020 of the COVID-19 Pandemic - Mactavish, Alexandra (J Can Acad Child Adolesc Psychiatry, 2021)
OBJECTIVE: COVID-19 presents an unprecedented global crisis. Research is critically needed to identify the impact of the pandemic on children’s mental health including psychosocial factors that predict resilience, recovery, and persistent distress. The present study collected data in June–July 2020 to describe children’s mental health during the initial phase of the pandemic, including the magnitude and nature of psychiatric and psychological distress in children, and to evaluate social support as a putative psychosocial moderator of children’s increased distress. METHOD: Children and parents from 190 families of children aged 8 to 13 from the Windsor-Essex region of Southwestern Ontario reported (i) retrospectively on children’s well-being (e.g., worry, happiness) immediately prior to the pandemic and (ii) on children’s current well-being; irritability; social support; and anxiety, depressive, and posttraumatic stress symptoms at the baseline assessment of an ongoing longitudinal study of the COVID-19 pandemic. RESULTS: Children and parents reported worsened well-being and psychological distress during the pandemic compared to retrospective report of pre-pandemic well-being. Child-perceived social support from family and friends was associated with lower symptom severity and attenuated increase in psychological distress. CONCLUSIONS: Study findings suggest possible broad psychological impacts of the COVID-19 pandemic and are consistent with prior research that indicates a protective role of social support to mitigate the negative psychological impact of the pandemic. These findings may inform clinical assessments and highlight the need for public resources to safeguard children’s mental health.